2002
DOI: 10.1046/j.1365-2044.2002.02750.x
|View full text |Cite
|
Sign up to set email alerts
|

Routine pre‐operative blood testing: is it necessary?

Abstract: SummaryIn order to determine the value of routine pre-operative screening investigations, the medical notes of 100 patients undergoing elective surgical procedures under general anaesthesia were subject to prospective audit. Pre-operative screening investigations (full blood count, urea and electrolytes and random glucose) were analysed in terms of frequency of abnormalities and whether or not the peri-operative management was changed when the result was abnormal. The frequency of results being present in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
63
0
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 10 publications
3
63
0
6
Order By: Relevance
“…Recent literature suggests that preoperative laboratory testing should be based on clinical examination rather than routine protocols [1][2][3][4][5][6]. Preoperative hemoglobin test or screening for anemia is included in most of the hospitals preoperative testing protocols in third world countries despite the fact that routine laboratory tests for all patients are not good screening device for diseases [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent literature suggests that preoperative laboratory testing should be based on clinical examination rather than routine protocols [1][2][3][4][5][6]. Preoperative hemoglobin test or screening for anemia is included in most of the hospitals preoperative testing protocols in third world countries despite the fact that routine laboratory tests for all patients are not good screening device for diseases [3].…”
Section: Introductionmentioning
confidence: 99%
“…These unexpected abnormal results have very little impact on the anesthetic management if at all [4,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous cohort study of 73,596 patients undergoing elective, low-risk ambulatory surgery, abnormal pre-anesthetic laboratory findings were not predictive of postoperative outcomes when compared with normal results [3]. Several studies have investigated the usefulness of preoperative screening tests in adult patients [4][5][6], however, there are scarce data for evaluation of routine pre-anesthetic AST and ALT testing in pediatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Preoperative evaluation is an area of practice where unnecessary expenses have been recognized. [7][8][9][10][11] Routine ordering of preoperative tests in the absence of specific indications rarely contributes to patient care and is not cost-effective. [7][8][9][10][11][12] A prior study of patients undergoing elective surgery showed that 60% of routinely ordered tests were unnecessary.…”
Section: Introductionmentioning
confidence: 99%